Makna Simbol Gelar Raja Dalam Masyarakat Adat Bali - Sangayu Ketut Laksemi Nilotama (Journal of Visual Art and Design, 2009)
Through the 18th and the 19th century, the position of Balinese King (Dewa Agung Jambe) was so important that he held power in both Bali and Lombok island, and he regognized by the title Sesuhunan Bali and Lombok. Dewa Agung Jambe politically and culturaly had several titles that were influential to the harmony of his sociaty livinghood. The titles of the king are related to the symbols that have sacred and trancendent meanings. Dewa Agung was God's Awatara, symbolized or varous forms such as ornaments, carvings, sacrad Balinese writings and letters, bulidings, even the deceased's container or coffin ( Bade beratap tumpang 11). The purpose of this essay was to explore the meanings and symbols that were the reflection of those king titles, to prevent the possibility of misuse from the original function of those sacred symbols. This has been a cultural research with the stucture of the history of Balinese Kingdom traditional sociaty that embranced Hindu. The funtion of these symbols are for strengthening the personality and morality, especialy in the aspect of arts and design. Therefore, it is important to continue preserving, harmonizing these tradisional symbols especially ones that have religious, sacrad, even spiritual values.